2021
DOI: 10.5194/hess-25-5337-2021
|View full text |Cite
|
Sign up to set email alerts
|

Preferential pathways for fluid and solutes in heterogeneous groundwater systems: self-organization, entropy, work

Abstract: Abstract. Patterns of distinct preferential pathways for fluid flow and solute transport are ubiquitous in heterogeneous, saturated and partially saturated porous media. Yet, the underlying reasons for their emergence, and their characterization and quantification, remain enigmatic. Here we analyze simulations of steady-state fluid flow and solute transport in two-dimensional, heterogeneous saturated porous media with a relatively short correlation length. We demonstrate that the downstream concentration of so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 65 publications
2
25
0
Order By: Relevance
“…This implies that the system ends in a dead state called thermodynamic equilibrium where all gradients have been depleted, corresponding to minimum free energy and maximum entropy. Open thermodynamic systems may however prevail in an organized state far away from the entropy maximum, if there is an external feedback sustaining a net influx of free energy to perform the necessary work to act against the depletion of gradients and to export the entropy produced during irreversible processes (Zehe et al, 2021). In the following we want to clarify this aspect for surface runoff and related ideas of thermodynamic optimality, which appear to be contradictory at first sight.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that the system ends in a dead state called thermodynamic equilibrium where all gradients have been depleted, corresponding to minimum free energy and maximum entropy. Open thermodynamic systems may however prevail in an organized state far away from the entropy maximum, if there is an external feedback sustaining a net influx of free energy to perform the necessary work to act against the depletion of gradients and to export the entropy produced during irreversible processes (Zehe et al, 2021). In the following we want to clarify this aspect for surface runoff and related ideas of thermodynamic optimality, which appear to be contradictory at first sight.…”
Section: Introductionmentioning
confidence: 99%
“…Although energy is conserved and cannot disappear due to the 1 st law of thermodynamics, free energy is not a conserved property, but is dissipated during irreversible processes due to the related production of entropy. Free energy is basically energy without entropy, and the free energy of a flow system is thus equivalent to its capacity to perform work to steepen a concentration gradient (Zehe et al, 2021) or to create motion in form of coupled water and sediment fluxes (Bagnold, 1966). Frictional dissipation during the latter implies production of heat through production of entropy, which increases the average kinetic energy of the molecules in the riverbed or the hillslope surface materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the description of heterogeneity and its representation in numerical models is one of the major challenges in hydrology. On the other hand, there seems to be an increasing number of studies attempting to derive preferred stated of the atmosphere and the hydrosphere from principles of optimality (e.g., Kleidon and Schymanski, 2008;Kleidon and Renner, 2013;Kleidon et al, 2014;Kleidon and Savenije, 2017;Kleidon et al, 2019;Zehe et al, 2010Zehe et al, , 2013Zehe et al, , 2021Westhoff and Zehe, 2013;Westhoff et al, 2014Westhoff et al, , 2017Zhao et al, 2016). In the context of fluid flow, minimum energy dissipation seems to be a promising concept, which was successfully applied to river networks (Howard, 1990;Rodriguez-Iturbe et al, 1992a, b;Rinaldo et al, 1992;Maritan et al, 1996) and to the cardiovascular system of mammals (West et al, 1997;Enquist et al, 1998Enquist et al, , 1999Banavar et al, 1999;West et al, 1999a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Berkowitz and Zehe (2020) underlined the need for additional studies to develop a unified theoretical framework comprising surface and subsurface water networks starting from a comprehensive analysis of fractal behaviors and (power-law based) statistical descriptions that are documented for these systems in diverse contexts. Leveraging on energy concepts, Zehe et al (2021) analyzed fluid flow and solute transport in (synthetically generated) randomly heterogeneous hydraulic conductivity fields and found that high solute concentrations associated with preferential pathways can be correlated with an elevated power in fluid flow therein.…”
Section: Introductionmentioning
confidence: 99%